Forced convection condensation in novel air-cooled fin tubes - Tan, Timothy Tze Yuan (Nanyang Technological University, 2021)
This report presents a numerical study of forced convection condensation heat transfer in a minichannel heat exchanger and an experimental study of single-phase forced convection heat transfer of a conventional fin-and-tube heat exchanger using R134a and air. A simulation was conducted using a 160-channel, minichannel heat exchanger with a hydraulic diameter,d_h, of 0.674 mm using R134a under saturation temperatures from 30°C to 50°C. Using a two-dimensional finite element analysis method, empirical correlations were implemented into a programming code in MATLAB to predict the overall heat transfer, pressure drop and heat transfer coefficient (HTC) of condensation of the minichannel tube. The simulation results were compared with existing data, where it showed satisfactory agreement among vapour qualities of 0.1 to 0.9. The experimental setup of a refrigerant-to-air test system was redesigned and modified to facilitate the experimental testing of both, minichannel and fin-and-tube, heat exchangers. A double-pipe heat exchanger was designed and fabricated for use as an evaporator. Leak tests were conducted for individual components of the refrigerant loop and the overall refrigerant loop. The overall refrigeration loop achieved a 0.24 bar/h leak rate. The single-phase HTC of a conventional fin-and-tube heat exchanger for two air velocities 7.535 m/s and 16.35 m/s were determined through the Wilson plot method to be 185 W/m2·K and 127 W/m2·K, respectively. Recommendations for future work are proposed to determine its condensation HTC to compare with that of the 160-channel minichannel heat exchanger.